2009
DOI: 10.1038/msb.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and controlling the reactivity of immune cell populations against cancer

Abstract: Heterogeneous cell populations form an interconnected network that determine their collective output. One example of such a heterogeneous immune population is tumor-infiltrating lymphocytes (TILs), whose output can be measured in terms of its reactivity against tumors. While the degree of reactivity varies considerably between different TILs, ranging from null to a potent response, the underlying network that governs the reactivity is poorly understood. Here, we asked whether one can predict and even control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…A recent report examining complex FACS profiles from TIL cultures predicted that the depletion of ''marker'' genes of unknown function from TIL could enhance IFN-g secretion in lymphocyte cultures in vitro. 38 The results we report may reflect a similar phenomenon, in that a few cells within the CD4 + population may have a disproportionate impact on the culture function and their removal may improve the systematic function of the culture.…”
Section: Discussionsupporting
confidence: 61%
“…A recent report examining complex FACS profiles from TIL cultures predicted that the depletion of ''marker'' genes of unknown function from TIL could enhance IFN-g secretion in lymphocyte cultures in vitro. 38 The results we report may reflect a similar phenomenon, in that a few cells within the CD4 + population may have a disproportionate impact on the culture function and their removal may improve the systematic function of the culture.…”
Section: Discussionsupporting
confidence: 61%
“…Hyporesponsiveness may occur even in effector T cells with enhanced expression of activation markers (HLA-DR and CD38) and low levels of BCL-2 [20,39]. The killing ability seems to be less affected [19,20,40] and degranulation (CD107a upregulation) by cytotoxic T cells may be normal [39] or diminished [41]. Recently, hyporesponsive self/tumor-specific T cells residing in metastases of melanoma patients were analyzed by gene expression profiling, revealing many more molecular alterations than just defective IFNg production [5].…”
Section: Cellular and Molecular Characteristics Of T Cell Hyporesponsmentioning
confidence: 99%
“…A bioinformatics study has shown that IFNg-positive and -negative T cells from melanoma metastases can be identified based on their expression of the activation marker CD69, the co-stimulatory molecule CD28, and the receptors CTLA-4 and CD94 [40]. An unfavorable balance of costimulatory and co-inhibitory signals in the tumor microenvironment is likely, because many tumors have been shown to lack co-stimulatory ligands and are enriched in co-inhibitory ligands [50].…”
Section: Reversibility Of Hyporesponsivenessmentioning
confidence: 99%
“…This can be done using machine learning (ML) methods, such as repertoire clustering by similarity [71], or the use of principal component analysis (PCA) to reduce data complexity and decision tree algorithms to find the features predicting, e.g., a treatment's outcome [12], to name just two examples. The use of ML tools can be demonstrated by our work on characterizing spectratype similarities and differences.…”
Section: Methods For Comparing Repertoires or Estimating Repertoire Smentioning
confidence: 99%
“…Studying B and T cell phenotypic repertoires is important for understanding the function of these cell subsets, how they change during aging, and the dysregulation leading to autoimmune diseases or lymphocyte malignancies [11]. The analysis of T cell repertoires based on cell surface markers has already yielded more insights than can be covered in this review; one interesting example would be the use of repertoire analysis for predicting and controlling the reactivity of immune cell populations against cancer [12]. With the improvements in multicolor flow cytometry, such analyses are bound to be performed in other types of lymphocytes.…”
Section: Introductionmentioning
confidence: 99%